Una storia di figure piccole, condotte con tanta arte e diligenza: “The Story of Orpheus” by Jacopo del Sellaio and Some Drawings from Filippino Lippi’s Workshop in the Uffizi Collection - Lopukhova, Marina A. (Actual Problems of Theory and History of Art, 2017)
A drawing by Filippino Lippi, which represents an old man singing and playing a lira da braccio (Florence, Uffizi Gallery, Gabinetto Disegni e Stampe, inv. 249E), evidently relates to the drawn images of musicians well known in Early Renaissance Florence. But the distinctive look and the ecstatic state of the man depicted make us search for a narrative in the drawing. Bernard Berenson interpreted it as an image of the King David. However, from the iconographical point of view, the model largely looks like Orpheus in the series of spalliera paintings by Jacopo del Sellaio which depict Angelo Poliziano’s Favola d’Orfeo (ca. 1490, separate partsare stored in museums of Rotterdam, Kiev, and Krakow). Stylistically, our drawing could be dated between the mid-1480s and the mid-1490s, close to the painted series, which are also similar to the drawings 232E and 1249E of the same collection made by other draughtsmen in the manner of Filippino. It is possible that these drawings from Filippino’s workshop could be free studies from the Sellaio’s paintings or, otherwise, two preparatory drawings for the series of panels on Orpheus’ story, which were finally commissioned to another master.
Keywords: Filippino Lippi; Jacopo del Sellaio; cassone painting; Florentine drawing; Orpheus